The Relationship Between Arm Muscle Strength And Shot Put Skills At Sdn 80 Central Bengkulu - Rini Rini; Martiani Martiani (Hanoman Journal: Physical Education and Sport, 2021)
This study aims to determine the relationship between arm muscle strength and shot put skills and to determine the relationship between bullet resisting skills at SDN 80 Central Bengkulu. So the population in this study were students of Class V SD Negeri 80 Central Bengkulu, amounting to 20 people. The results showed that through a simple correlation test, the rcount value of 0.767 was greater than the rtable value with N 20 with a value of rxy = 0.767 r (0.05) n (11) = 0.444 and a significant level of 0.05, which is Lo 0.767 Ltable 0.444 for Arm Muscle Strength and Lo 0.576 Ltable 0.444 for the ability to put down bullets.